Dawn Raffel–A Family Portrait - Monica Manolescu-Oancea (Transatlantica)
This article wishes to examine the literary genealogy of Dawn Raffel and to explore the notion of intertextuality as well, together with the critical debate surrounding it. A tentative family portrait will be drawn through the study of the short story collection In the Year of Long Divsion (1994), with references to the novel Carrying the Body (2002).